Carbon/carbon high thickness shell for advanced space vehicles. (January 2019) - Albano, M.; Alifanov, O.M.; Budnik, S.A.; Morzhukhina, A.V.; Nenarokomov, A.V.; Titov, D.M.; Gabrielli, A.; Ianelli, S.; Marchetti, M.
Highlights: Experimental and theoretical methodology for data acquisition of unsteady thermal state. Description of test equipment and the algorithm for solving the inverse heat conduction problem. Study of carbon/carbon shell for its use as hot structure in application such as windward connections. Abstract: The aim of this paper is to study a shell structure for space applications. The aim of the structure is to be reusable and thick. This first study will focus on thermal environment. Starting from a defined geometry, a prototype will be manufactured. Thermo-structural behavior of the structure will be analyzed by numerical analysis and tests. Thermal properties, such as thermal conductivity and heat capacity, will be studied by the use of the inverse method. A robust numerical approach, such as inverse method, is one of the best for this problem as many parameters concur for the determination of properties. Such approach permits to perform the parametric and structural identification of the model. These procedures are presented including both experimental investigation and methodical-numerical aspects. Special test equipment and the regularizing algorithm for solving the ill-posed inverse heat conduction problem are described. In the frame of thermal properties determination, a verification and prediction of thermocouple error will be performed. Developed in the frame of this work the experimental and theoretical methodology for complex data acquisition of unsteady thermal state of the prototype of shell structure is proposed.